UPAYA PENINGKATAN KAPASITAS IBU DALAM PELAKSANAAN IMUNISASI DI ERA NEW NORMAL DI KOTA BANJARBARU - yuniarti, yuniarti; Rusmilawaty, Rusmilawaty; Tunggal, Tri (UPPM Poltekkes Kemenkes Banjarmasin, 2023)
Routine immunizations that are carried out continuously and continuously, consist of basic and advanced immunizations. Basic immunization is given to babies before the age of 1 year. The purpose of this activity is to increase the understanding and knowledge of mothers and families about immunization and reduce anxiety about the implementation of immunization in the new normal era. The target audience is mothers of infants aged 0-3 months totaling 75 people. The initial stage of the activity carried out was to convey material on immunization in infants and how to overcome maternal anxiety in the new normal era using lecture, discussion, direct question and answer, and leaflet distribution methods. The second stage is to assist mothers in the implementation of immunization as one of the supports and overcome the anxiety of mothers in the new normal era to bring their children to immunization. And at the final stage of the activity an evaluation is carried out which consists of Evaluation after community service activities to determine the target's understanding of immunization administration and how to overcome maternal anxiety using a questionnaire. Evaluation of activities carried out after 1 month and 3 months of implementation of activities to determine the achievement of immunization in infants in the new normal era. Results At the initial stage, a pretest was conducted about immunization, there were 34 mothers (45.3%) with good knowledge about immunization, 39 mothers (52%) with sufficient knowledge and 2 mothers (2.7%) had poor knowledge about immunization. After 3 months of mentoring and counseling, it appears that the mother's knowledge has increased. In the pre-test of the mother's knowledge level, an average of 52% had sufficient knowledge about immunization. While in the post-test the mother's knowledge increased, to 68% with good knowledge. So it can be concluded that the mother's understanding and knowledge of immunization increased and the mother's anxiety was reduced by the mother understanding about the procedure for implementing immunization in the new normal era and willing to bring her child to the health center for immunization.